Competition and Firm Productivity : Evidence from Firm-Level Data - Schiffbauer, Marc.; Ospina, Sandra (Washington, D.C. : International Monetary Fund, 2010)
This paper presents empirical evidence on the impact of competition on firm productivity. Using firm-level observations from the World Bank Enterprise Survey database, we find a positive and robust causal relationship between our proxies for competition and our measures of productivity. We also find that countries that implemented product-market reforms had a more pronounced increase in competition, and correspondingly, in productivity: the contribution to productivity growth due to competition spurred by product-market reforms is around 12-15 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet